LASKAR SEHAT LATIHAN KADER AKTIF DAN SIAGA UNTUKKESEHATAN MASYARAKAT - Nur Aini Febrianti; Rini Nurul Hidayah; Devy Febriyani Widyastuti; Wanda Gustia; Danar Firdaus Bondan Prakoso; Dea Aurela Herawan; Sumarni (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Posyandu and Posbindu cadres play an important role in improving community health. However, in Loa Pari Village, Tenggarong Seberang District, many cadres have never received proper training, resulting in limited knowledge and skills in carrying out health services. Through the “Laskar Sehat (Cadre Training)” program, this activity aims to enhance the capacity and competence of cadres in delivering basic health services. After the training, cadres are expected to become more skilled, independent, and actively contribute to creating a healthier and more empowered community in Loa Pari Village. Objective : The LASKAR SEHAT was implemented to enhance the capacity and competency of Posyandu (Integrated Service Post) cadres, particularly those serving at Posyandu Lansia Kenanga 1 and Posbindu PTM. The activities involved direct educational sessions and the distribution of an educational pocketbook designed to strengthen the cadres’ knowledge and practical skills. Through these efforts, the program aimed to develop active, competent, and well-prepared cadres capable of performing promotive and preventive public health functions within Loa Pari Village. The success of the program was measured by comparing the participants’ pre-test and post-test scores. Research Methods/ Implementation Methods : The Community Field Learning I activity by Public Health students of Group 12 was held on July 9, 2025, at Loa Pari Village Hall, Tenggarong Seberang District, Kutai Kartanegara. This program included health education and training for nine Posyandu Lansia and Posbindu PTM cadres on non-communicable diseases, anthropometric measurements, BMI calculation, blood pressure monitoring using a digital tensimeter, and completing elderly health monitoring books. The activity consisted of four stages: pre-test, health education and booklet distribution, practical training, and post-test to evaluate the improvement of the cadres’ knowledge and skills in understanding the materials and using health equipment. Results : The increase in knowledge of Laskar Sehat participants from before counseling to after counseling is equal to a significant improvement, reflecting the effectiveness of the health education provided in enhancing their understanding and awareness.